Improving knowledge exchange among scientists and decision-makers to facilitate the adaptive governance of marine resources: A review of knowledge and research needs. (August 2015) - Cvitanovic, C.; Hobday, A.J.; van Kerkhoff, L.; Wilson, S.K.; Dobbs, K.; Marshall, N.A.
Abstract: The science-based management of natural resources requires knowledge exchange between scientists and environmental decision-makers, however, this exchange remains a significant challenge. Rather, evidence suggests that decision-makers rely on individual experience or other secondary sources of knowledge in isolation from scientific evidence when formulating decisions, potentially compromising the effectiveness of their decisions. As a result a new field of research broadly characterised as 'knowledge exchange' has emerged, focused largely on identifying and overcoming the barriers to knowledge exchange among scientists and decision-makers. More recently knowledge exchange research has also begun to explore the relationship between science and decision-making specifically in relation to marine ecosystems and resources. The aim of this paper is to review the literature in relation to knowledge exchange for natural resource management, with a focus on recent evidence in relation to the management of marine resources. This review identifies critical barriers inhibiting knowledge exchange among marine scientists and decisions-makers, such as the inaccessibility of science to decision-makers as well as institutional barriers that limit the extent to which scientists and decision-makers can prioritise knowledge exchange activities. Options for overcoming these barriers, such as novel approaches to knowledge exchange (e.g. – knowledge co-production, knowledge brokers and boundary organisations) and the enabling environments and institutional reforms needed to complement efforts to improve knowledge exchange, are also identified. This review concludes by articulating the gaps in our understanding of knowledge exchange, to help guide future research in this field and improve the sustainable management of marine resources. Highlights: Integration of science into marine management decisions is a significant challenge. Adaptive governance of marine resources depends on timely knowledge exchange. Institutional impediments and science inaccessibility limit knowledge exchange. Improved knowledge exchange can occur through formal and informal structures. Strategies for improved knowledge exchange are discussed.